THE IMPACT OF IMPLEMENTING THE INDEPENDENT CURRICULUM BASED ON DEEP LEARNING LEARNING TO IMPROVE STUDENTS' CREATIVITY AND RELIGIOUS CHARACTER IN THE DIGITAL ERA - Jamiatussholihah; Rofiatul Hosna; Khoirotul Idawati (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
The aim of this study is to analyze and empirically measure the magnitude of the influence of the implementation of the Independent Curriculum based on deep learning on improving students' creativity and religious character in the digital era. This study used a quantitative approach with a survey method on 67 students selected through simple sampling. A random sampling method was used from a population of 199 students. Data were collected through a 32-item closed-ended questionnaire using a four-point Likert scale . Analysis was conducted using validity, reliability, and linear regression tests using SPSS at a significance level of 0.05 to examine the impact of the implementation of the Independent Curriculum based on deep learning. learning on students' creativity and religious character. The results of the study show that the implementation of the Independent Curriculum is based on deep Learning has a positive and significant effect on students' creativity and religious character. The results of the regression test showed a significant effect on students' creativity (B = 0.342; t = 10.63; Sig . = 0.000) with a contribution of 46.5% (R² = 0.465), as well as on students' religious character (B = 0.340; t = 10.23; Sig . = 0.000) with a contribution of 42.6% (R² = 0.426). The average score of curriculum implementation is in the high category ( Mean = 52.47), followed by students' creativity ( Mean = 26.15) and students' religious character ( Mean = 27.03). These findings confirm that meaningful, reflective, collaborative learning, and ethically oriented technology integration are empirically able to improve students' cognitive and moral dimensions simultaneously in the digital era